Translocator protein in the rise and fall of central nervous system neurons - Cheung, Garett; Lin, Yiqi Christina; Papadopoulos, Vassilios (Frontiers in Cellular Neuroscience, 2023)
Translocator protein (TSPO), a 18kDa protein found in the outer mitochondrial membrane, has historically been associated with the transport of cholesterol in highly steroidogenic tissues though it is found in all cells throughout the mammalian body. TSPO has also been associated with molecular transport, oxidative stress, apoptosis, and energy metabolism. TSPO levels are typically low in the central nervous system (CNS), but a significant upregulation is observed in activated microglia during neuroinflammation. However, there are also a few specific regions that have been reported to have higher TSPO levels than the rest of the brain under normal conditions. These include the dentate gyrus of the hippocampus, the olfactory bulb, the subventricular zone, the choroid plexus, and the cerebellum. These areas are also all associated with adult neurogenesis, yet there is no explanation of TSPO’s function in these cells. Current studies have investigated the role of TSPO in microglia during neuron degeneration, but TSPO’s role in the rest of the neuron lifecycle remains to be elucidated. This review aims to discuss the known functions of TSPO and its potential role in the lifecycle of neurons within the CNS.